Damage Detection Based on Recorded Damaged Natural Frequencies Using Binary Bat Algorithm - Richard Frans; Yoyong Arfiadi (Fakultas Teknik, Universitas Katolik Widya Mandala Surabaya, 2026)
The health monitoring system cycle for a structure has a significant impact on damage detection. The life cycle of a structure can be improved through the implementation of effective damage detection techniques. This is because the identification, prevention, and repair of damaged structural elements can be conducted with precision and speed. This study suggests a technique for identifying structural components that have been damaged. This approach involves comparing the recorded natural frequency to its actual natural frequency for all potential damage scenarios. The Modal Assurance Criterion (MAC) has been used to compare these two natural frequency values, while a binary value is used to indicate whether an element has been damaged or not. Two types of structures are considered: (1) shear building structures and (2) plane truss structures. Several damage scenarios are used to test the accuracy of the proposed method. According to the results, the binary bat algorithm in conjunction with MAC produces accurate results for the two categories of structures examined under several kinds of damage scenarios, such as single, double, and multiple damage.